Occupational health and safety regulations in China: development process, enforcement challenges, and solutions - Xu, Xinyu; Ren, Peihua; Shi, Wenyan; Deng, Feidan; Wang, Qingfeng; Shi, Shaoteng; Shen, Jingchun; Dong, Guoqiang; Han, Jing (Frontiers in Public Health, 2025)
BackgroundOccupational health is closely related to China’s public health system and the construction of a healthy China. The purpose of this paper is to summarize the current health status of China’s occupational population and the dilemmas faced by prevention and treatment work.MethodsThe following databases were utilized: China National Knowledge Infrastructure (CNKI), Wanfang Data, PubMed, Web of Science, Scopus, and Google Scholar. Keywords used included “occupational health,” “occupational hygiene,” “occupational disease prevention,” “occupational risks,” “occupational health regulations,” and “China.” The search was limited to articles published from 2000 to the present to ensure the inclusion of the most recent studies and regulatory updates.ResultsIt is found that changes in industrial structure have led to significant differences in the production environment and labor practices of different occupations, which in turn have triggered the gradual emergence of various types of occupational diseases. The existing legislative system of occupational diseases protects the rights and interests of workers to a certain extent, but there are still some shortcomings. The main dilemmas faced by the prevention and control work include the complexity and diversity of occupational disease hazards, the lack of implementation of prevention and control measures, and the imperfection of the legislative system.ConclusionThis study proposes directions and measures for good prevention and control of occupational diseases, and explores the road of prevention and control of occupational diseases with Chinese characteristics. By improving the legislative guarantee, optimizing the implementation mechanism, and deepening the social co-governance, a sustainable occupational health management system adapted to the needs of industrial upgrading will eventually be constructed.